Trastorno de ansiedad generalizada como factor de riesgo para obesidad en pacientes adultos del centro de atención primaria ii otuzco - essalud 2014 - Serrano García, Blanca Rosa (2015)
During the consultation for obesity, patients often refer eat for anxiety. DSM-IV defines the generalized anxiety disorder (GAD) as an excessive anxiety and worry for different events during most of the days for at least 6 months. Obesity is a global public health problem that has increased to over the years by the impact it has on life expectancy. Its incidence varies from a specific group to another and grows from year to year. Therefore it was considered necessary to determine whether if the presence of generalized anxiety disorder is a risk factor for obesity in adults Primary Care Center II Otuzco- EsSalud. The sample consisted of 180 users, from 18 to 60 years (45 cases and 135 controls) who met the inclusion and exclusion criteria matched for age and sex. Simple random sampling and case control analytical design was used. The TAG detection scale was used according to DSM-IV. The results of this study show first, that from the 45 obese patients 31 (68.9%) had generalized anxiety which score was ≥ 4 points and 14 (31.1%) had no generalized anxiety; second , from the 135 non-obese patients, 36 (26.7%) had generalized anxiety and 99 (73.3%) no generalized anxiety. Therefore these values with the possible presence of an anxiety disorder are significantly associated with the condition of obesity which results are for X 2 = 25.7482, p <0.001 and OR = 6.09 . being this greater than one, it was determined 95% confidence interval (2.91 - 12.73) to confirm association of exposure to the disease. This result demonstrates, the association between obesity and generalized anxiety disorder .Besides, during the facing of these patients not only have to worry about body weight and risk factors, but also is necessary to assess the psychological state.